PEMBELAJARAN KARAKTER MELALUI KEBIASAAN HARIAN DI PONDOK PESANTREN AL MASHDUQIAH - Khairul Anam, Rifqi; Almas Kistina, Sabila; Zahro Maulidiya, Luluk; Amelia, Fita (As-Sulthan Journal of Education, 2026)
Character education through daily habits at Pondok Pesantren Al Mashduqiah plays a highly significant role in shaping the students' character. This research aims to analyze the influence of daily habits, such as congregational prayer (sholat berjamaah), cleaning duty, and time discipline, on the character formation of students at the Islamic boarding school. The method employed is a mixed-methods approach, combining library research with field observation to delve deeper into the habits implemented in the pesantren and their impact on the students' character. Data were collected through direct observation of students' daily activities and interviews with pesantren administrators. The findings indicate that the habits of congregational prayer, religious study activities (pengajian), and time discipline consistently contribute to the formation of disciplined character, responsibility, and a sense of solidarity among students. Furthermore, the dormitory environment, which supports intense social interaction, also accelerates the internalization of taught moral values, making character education more effective. In conclusion, daily habituation at Pondok Pesantren Al Mashduqiah provides an important contribution to forming individuals with noble morals and responsibility, as well as creating an environment that supports the development of students' character in various aspects of life.